The IUCN red list for ecosystems: how does it compare to South Africa's approach to listing threatened ecosystems? - Monyeki, Maphale Stella (Department of Statistical Sciences, 2022)
The publication of the International Union for Conservation of Nature (IUCN) Red List of Ecosystems (RLE) standards is an important development that has received broad acceptance globally. More than 100 countries across the globe including South Africa and Myanmar have adopted the IUCN RLE standards as their national framework for assessing the risk of ecosystem collapse. The strongest motivations for the alignment include: (i) elimination of confusion and reducing the administrative burden for maintaining multiple lists of threatened ecosystems, (ii) increased legitimacy of the ecosystem threat status assessment by basing them on a body of sound scientific literature, (iii) comparable assessments across different environments and countries across the globe, (iv) for the threatened national ecosystems to be recorded under the IUCN RLE registry. Furthermore, the IUCN Red List makes it easier for countries to secure funding from international donors to achieve national biodiversity conservation objectives, and address knowledge and data gaps through focused research. The IUCN RLE standards only became available after many countries including South Africa and Australia each independently tailor-developed national indicators or standards for assessing threats to ecosystems. The Ecosystem Threat statuses (ETS) standards are developed to aid biodiversity monitoring efforts, and many have progressed into the legislated national list of the threatened ecosystems. In South Africa, the gazetted list of threatened ecosystems is ratified to inform policy development and land-use planning tools that mainstream biodiversity considerations into economic development activities. Considering the strong links between the gazetted list of threatened ecosystems and many of the policy and spatial planning tools, the change and/or update to the IUCN RLE standards may disrupt conservation and land-use plans. In addition, South Africa has limited data on ecosystem integrity with to apply the full range of the IUCN RLE functional criteria which may lead to the risk of ecosystem collapse being underestimated. However, the country has comprehensive data on threatened plant species which in many cases contain detailed information on drivers of environmental degradation and biotic disruptions. In addition, extensive efforts have been made to link threatened species and the ecosystem types in which they occur. Such efforts enable the country to look at degradation through species lenses to better understand the degree of underestimation of ecosystem risk. Nonetheless, there is a need to interrogate and holistically understand the implications that may emanate from this shift, hence the importance of this study. This thesis was focused on assessing the origins and history of the IUCN and South Africa's approach to assessing threats to ecosystems. In chapter 1, I reviewed the key concepts including the scientific basis and criteria to understand the purpose and philosophy of the South Africa (SA) ETS and IUCN RLE frameworks. In Chapter 2, I compared and contrasted the SA ETS and IUCN RLE assessment outcomes of ecosystems susceptible to only spatial threats. Finally, in Chapter 3, I tested whether the IUCN RLE is a good proxy for the distribution of threatened species in South Africa. The results revealed that the IUCN RLE and SA ETS standards have overarching similarities (e.g. spatial and functional criteria) as they both share the common ancestry (IUCN Red List of Threatened Species). Equally, there are key differences (e.g. decision thresholds) that explain the misalignments in the ecosystem threat status between the two systems. Meanwhile, the quantitative results alluded that the proportions of matching assessment outcomes are high when the risk categories (Critically Endangered: CR and Endangered: EN versus Vulnerable: VU and Least Concern: LC) are split in accordance with their policy uptake (i.e. National Environmental Management Act (NEMA) EIA regulations) but relatively low per individual risk category. Furthermore, the results suggest that not all ecosystem types undergoing spatial declines entirely reflect the status of threatened plant species they contain. Many of these threatened plant species overlap with ecosystems at immediate risk of collapse (CR and EN). Such species will indirectly benefit from broad-scale conservation interventions that are informed by the list of threatened ecosystems. However, the majority of plant species threatened by either habitat loss and/or land degradation occur within the least threatened ecosystems. These species will not benefit from conservation responses informed by the gazetted national list of threatened because spatial declines within these ecosystems are considered to either be minimal or stable to trigger conservation response. Encouragingly, there are existing legal conservation tools such as stewardship programmes, Key Biodiversity Areas, and Critical Biodiversity Areas that allow threatened and unprotected ecological features including species to be strategically targeted for conservation responses. However, there is a need for South Africa to intensify efforts that ensure that these legal tools are implemented correctly and successfully to maximise conservation impacts and arrest biodiversity loss.